Do constitucionalismo do comum às lutas cosmotécnicas: constituição do comum e lutas cosmotécnicas: From common constitutionalism to cosmotechnical struggles: constitution of the common and insurrection processes - Bolzán de Morais, José Luis; Hoffmam, Fernando (Araucaria, 2024)
The purpose of this article is to understand the transition from a constitutionalism of the common – already proposed previously – to the field of cosmotechnical struggles, in the sense that it would no longer be possible to think and constitute a cosmopolitical project except from them. To this end, what is proposed, based on the limits and crises of State and the constitutionalism that accompanies it, seek the construction of cosmopolitical projects through the resizing of constitutionalism, proposing this in the work from the perspective of the common and human rights, it is essential constitute the common beyond the limits of constitutionalism – state-based or not – since the constitution of the common today takes place in a field in dispute over techno-political practices through cosmotechnical struggles and processes of insurrection, against the backdrop of the impacts of globalization neoliberalism and the disruption of the digital age.